Ethical Considerations on Disclosure When Medical Error Is Discovered During Medicolegal Death Investigation. (December 2017) - Wolf, Dwayne A.; Drake, Stacy A.; Snow, Francine K.
Abstract : Abstract: In the course of fulfilling their statutory role, physicians performing medicolegal investigations may recognize clinical colleagues' medical errors. If the error is found to have led directly to the patient's death (missed diagnosis or incorrect diagnosis, for example), then the forensic pathologist has a professional responsibility to include the information in the autopsy report and make sure that the family is appropriately informed. When the error is significant but did not lead directly to the patient's demise, ethical questions may arise regarding the obligations of the medical examiner to disclose the error to the clinicians or to the family. This case depicts the discovery of medical error likely unrelated to the cause of death and describes one possible ethical approach to disclosure derived from an ethical reasoning model addressing ethical principles of respect for persons/autonomy, beneficence, nonmaleficence, and justice.